Metabolomic and cultivation insights into the tolerance of the spacecraft-associated Acinetobacter toward Kleenol 30, a cleanroom floor detergent - Mogul, Rakesh; Miller, Daniel R.; Ramos, Brian; Lalla, Sidharth J. (Frontiers in Microbiology, 2023)
Stringent cleaning procedures during spacecraft assembly are critical to maintaining the integrity of life-detection missions. To ensure cleanliness, NASA spacecraft are assembled in cleanroom facilities, where floors are routinely cleansed with Kleenol 30 (K30), an alkaline detergent. We show that cultures of spacecraft-associated Acinetobacter tolerate up to 1% v/v K30 and are fully inhibited at ≥2%; in comparison, NASA cleanrooms are cleansed with 0.8% K30. For A. johnsonii 2P08AA (isolated from a spacecraft assembly facility floor), cultivations with 0.1% v/v K30 exhibited (1) no changes in cell density at late-log phase, (2) modest decreases in growth rate (~17%), (3) negligible times in the lag phase, (4) limited changes in the intracellular metabolome, and (5) increases in extracellular sugar acids, monosaccharides, organic acids, and fatty acids. For the 50v1 strain (isolated from a pre-flight spacecraft surface), cultivations exhibited (1) ~50% survivals, (2) no changes in growth rate, (3) ~70% decreases in the lag phase time, (4) differential changes in intracellular amino acids, compatible solutes, nucleotide-related metabolites, dicarboxylic acids, and saturated fatty acids, and (5) substantial yet differential impacts to extracellular sugar acids, monosaccharides, and organic acids. Together, these results indicate that (1) K30 manifests strain-dependent impacts on the survivals, cultivation kinetics, and intracellular metabolomes, (2) K30 influences extracellular trace element acquisition in both strains, and (3) K30 is better tolerated by the floor-associated strain. Hence, these trends support the hypothesis that repeated cleansings during spacecraft assembly serve as selective pressures that promote tolerances towards the cleaning conditions.